2020
DOI: 10.24036/pelitaeksakta/vol3-iss2/117
|View full text |Cite
|
Sign up to set email alerts
|

Study of Assistance Development of Thematic Learning Material by Integrating New Literacy and Disaster Literacy on Science Teachers

Abstract: The 4.0 industrial revolution requires humans to possess 21st century skills. Education should be able to prepare students to have 21st century skills to be successful in their life. In addition, the geographical condition of Indonesia is a disaster-prone region. For this reason, teaching should be able to develop student literacy to face the challenges of the industrial revolution 4.0 and the geographical condition of the Indonesian region. The thematic science teaching is relevant to 21st century skills, ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…From the analysis that has been done, it is found that the product developed can improve students' technology literacy skills. The research data shows differences between the control and experimental groups on indicators of the use of electronic learning resources, even though the use of electronic learning resources is one manifestation of students' literacy skills (Asrizal, 2020). Technology literacy can be improved by using DTM as learning resources and using virtual laboratories to conduct experiments (Arista & Kuswanto, 2018;Brata et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…From the analysis that has been done, it is found that the product developed can improve students' technology literacy skills. The research data shows differences between the control and experimental groups on indicators of the use of electronic learning resources, even though the use of electronic learning resources is one manifestation of students' literacy skills (Asrizal, 2020). Technology literacy can be improved by using DTM as learning resources and using virtual laboratories to conduct experiments (Arista & Kuswanto, 2018;Brata et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Learning materials are needed to support the integration of STEM into science and physics learning. The definition of the learning material itself is the substance of the lesson that is arranged systematically so that it can bring out what students have [30]. Learning materials are useful to facilitate students and teachers in carrying out learning activities [31].…”
Section: Introductionmentioning
confidence: 99%
“…Information literacy is the ability to read, analyze and use or utilize information in the advanced world [3]. Technological literacy is a continuation of advanced literacy which emphasizes the importance of social media and the use of technology in life, especially in the field of education [2]. Where is the age of advanced literacy, namely the ability to determine and access a variety of information in computerized technology [4].…”
Section: Introductionmentioning
confidence: 99%
“…Learning with STEM education is very important because it provides training to students so that they can integrate every aspect. So that the learning process that includes these four aspects will form a more comprehensive knowledge of the subject being studied [2]. This means the implementation of a comprehensive integrated learning plan that includes the details of the learning procedures.…”
Section: Introductionmentioning
confidence: 99%